Digital financial literacy and microfinancing among underprivileged communities in Cambodia - Banciu, Doina; Arulanandam, Benedict Valentine*; Munhenga, Trymore; Ivascu, Larisa (National Institute for Research and Development in Informatics, 2022)
This research uses an exploratory approach to evaluate digital financial literacy education and its impact on financial knowledge and financial behavior of rural residents. The villages in Siem Reap province were selected for this analysis, both for the provision of digital financial literacy education and for the measurement of digital financial literacy with the purpose of determining their impact on reducing poverty. This study reveals that access to financial inclusion services has extended and the low levels of literacy and financial literacy of the people in the selected villages have contributed to their unsustainable financial habits and in the end, they led to over indebtedness. A new approach to digital institutional economics was introduced as a tool for the evaluation of microfinancing. The institutionalization of financial inclusion strategies to incorporate financial literacy and the adherence to the laws of financial markets and the commercialization of operations are in order to pave the way for individual financial well-being, institutional growth, and sustainable economic development.